An Empirical View of Business Ethics on Press Freedom: A Case Study - Kamarudin, Diyana; Azizul, Faiz; Khairul Anuar Wan Abd Manan, Wan (KnE Social Sciences, 2019)
Press freedom in Malaysia is bound under several regulations and restrictions ever since Malaysia granted independence in 1957. Due to this, a few media and press laws were also inadvertently inherited from the draconian colonial law or introduced in controlling any extremist actions during emergency periods and also used in silencing any political rivals. Based on the report compiled by Reporters without Borders (RSF), Malaysia jumped 22 places to 123